Regulation of the Abundance of Kaposi's Sarcoma-Associated Herpesvirus ORF50 Protein by Oncoprotein MDM2. - Tzu-Hsuan Chang; Shie-Shan Wang; Lee-Wen Chen; Ying-Ju Shih; Li-Kwan Chang; Shih-Tung Liu; Pey-Jium Chang (PLoS Pathogens)
The switch between latency and the lytic cycle of Kaposi's sarcoma-associated herpesvirus (KSHV) is controlled by the expression of virally encoded ORF50 protein. Thus far, the regulatory mechanism underlying the protein stability of ORF50 is unknown. Our earlier studies have demonstrated that a protein abundance regulatory signal (PARS) at the ORF50 C-terminal region modulates its protein abundance. The PARS region consists of PARS-I (aa 490-535) and PARS-II (aa 590-650), and mutations in either component result in abundant expression of ORF50. Here, we show that ORF50 protein is polyubiquitinated and its abundance is controlled through the proteasomal degradation pathway. The PARS-I motif mainly functions as a nuclear localization signal in the control of ORF50 abundance, whereas the PARS-II motif is required for the binding of ubiquitin enzymes in the nucleus. We find that human oncoprotein MDM2, an ubiquitin E3 ligase, is capable of interacting with ORF50 and promoting ORF50 degradation in cells. The interaction domains between both proteins are mapped to the PARS region of ORF50 and the N-terminal 220-aa region of MDM2. Additionally, we identify lysine residues at positions 152 and 154 in the N-terminal domain of ORF50 critically involved in MDM2-mediated downregulation of ORF50 levels. Within KSHV-infected cells, the levels of MDM2 were greatly reduced during viral lytic cycle and genetic knockdown of MDM2 in these cells favored the enhancement of ORF50 expression, supporting that MDM2 is a negative regulator of ORF50 expression. Collectively, the study elucidates the regulatory mechanism of ORF50 stability and implicates that MDM2 may have a significant role in the maintenance of viral latency by lowering basal level of ORF50.